2004
DOI: 10.1016/j.jviromet.2004.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of the coronavirus that induces severe acute respiratory syndrome, SARS-CoV

Abstract: Severe acute respiratory syndrome (SARS) is a life-threatening disease caused by a novel coronavirus termed SARS-CoV. Due to the severity of this disease, the World Health Organization (WHO) recommends that manipulation of active viral cultures of SARS-CoV be performed in containment laboratories at biosafety level 3 (BSL3). The virus was inactivated by ultraviolet light (UV) at 254 nm, heat treatment of 65 degrees C or greater, alkaline (pH > 12) or acidic (pH < 3) conditions, formalin and glutaraldehyde trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

36
733
3
18

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 686 publications
(790 citation statements)
references
References 25 publications
36
733
3
18
Order By: Relevance
“…The virus could not be inactivated at a low temperature of 4°C even after 3 days. However, when using a higher temperature of 25 or 37°C, formaldehyde could inactivate most of the virus after 1 day [30]. Although not investigated in this particular study, in addition to temperature, the pH during inactivation can play a major role, as is further illustrated in this review (see 'pH' section).…”
Section: Reviewmentioning
confidence: 81%
See 4 more Smart Citations
“…The virus could not be inactivated at a low temperature of 4°C even after 3 days. However, when using a higher temperature of 25 or 37°C, formaldehyde could inactivate most of the virus after 1 day [30]. Although not investigated in this particular study, in addition to temperature, the pH during inactivation can play a major role, as is further illustrated in this review (see 'pH' section).…”
Section: Reviewmentioning
confidence: 81%
“…It is also possible that the safety testing was not sufficient and that a higher concentration of formaldehyde is necessary to inactivate these viruses properly. Darnell et al examined formaldehyde inactivation of the severe acute respiratory syndrome coronavirus (SARSCoV) [30]. They showed that formaldehyde can inactivate the virus in a temperaturedependent manner.…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations